Роль проєктного менеджера в проєкнтно-орієнтованих організаціях - Когут, Ірина Василівна; Kohut, Iryna (Запоріжжя : Видавничий дім «Гельветика», 2025)
UA: У статті розглядаються особливості проєктно-орієнтованих організацій та місце проєктного менеджера в їх структурі. Здійснено огляд сучасних наукових підходів до визначення поняття проєктно орієнтованої організації, проаналізовано ключові характеристики таких підприємств. Особливу увагу приділено ролі менеджера проєкту як критично важливого елемента успіху проєктів і конкурентоспроможності компанії. У контексті сучасних викликів обґрунтовано доцільність використання моделі зрілості управління проєктами (PMMM) Г. Керцнера для аналізу трансформації ролі проєктного менеджера на різних етапах розвитку організації. Результати дослідження дозволяють уточнити визначення проєктно-орієнтованої організації та окреслити траєкторії розвитку потенціалу проєктного менеджера. /// EN: This paper investigates the distinctive features of project-oriented organizations (POOs) and the evolving role of project managers within them. The findings indicate that POOs are dynamic and better equipped to adapt to change compared to traditional organizations. Their development is largely driven by innovation, knowledge management, and project management methodologies. Analysis of various academic perspectives demonstrates that the understanding of project-oriented organizations has evolved over time from being viewed as a set of processes to encompassing organizational values, culture, and knowledge sharing. Within these organizations, the project manager plays a central role – not merely as an executor but as a leader and team motivator who contributes strategically to organizational growth and transformation. The Project Management Maturity Model (PMMM) developed by Harold Kerzner was employed as a framework to analyze the evolution of project-oriented organizations and the transformation of the project manager’s role. This model clearly illustrates the correlation between the maturity level of the organization and the professional maturity of the project manager. As organizations mature, the project manager’s responsibilities shift from operational tasks to strategic influence, including vision development, team integration, and ensuring long-term sustainability. Despite increased interest in the human factor in project management practice and theory, there remains a lack of structured research on the potential and professional development of project managers in Ukrainian project oriented organizations. This presents opportunities for future academic inquiry and practical improvement of project management approaches. Thus, an enhanced understanding of project-oriented organizations and the recognition of the project manager’s role as an integrator of knowledge, strategies, and team efforts is crucial for the successful operation of modern companies in an unstable environment. This highlights the need for more structured research into the professional development of project managers in Ukraine, especially considering their influence on organizational resilience and long-term success.
The role of the project manager in project-oriented
Keywords: проєктно-орієнтовані організації; мотивація проєктних менеджерів; організаційна зрілість; Project Management Maturity Model; роль проєктного менеджера; project-oriented organizations; motivation of project managers; organizational maturity